Stress and Job Performance of Healthcare Workers amidst COVID-19 Pandemic: The Mediating Role of Burnout - Tri Siwi Agustina; Putri Dian Rarastanti; Arif Fatah Hidayat (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Healthcare workers in hospitals are one of the frontliners in handling the COVID-19 issue. However, previous studies were mostly directed on doctors and nurses, albeit many other workers are involved in managing the COVID-19 issue at a hospital. Physical and mental work pressures in performing their jobs and responsibilities potentially affect their performance. This study aims to shed some light on the direct influence of job stress on the job performance of healthcare workers during the COVID-19 pandemic with burnout as a mediating variable. This study make use of a cross-sectional approach by employing a questionnaire to gather the data from 194 healthcare workers at Aisyiyah Ponorogo General Hospital Indonesia. Drawing on the Structural Equation Modeling Partial Least Square, the results reveal that (1) job stress has a negative influence on the job performance of the healthcare workers, (2) job stress is proven to have a positive effect on the burnout of the healthcare workers, and (3) burnout is found to partially mediate the effect of job stress on the job performance of the healthcare workers. By referring to the compelling results, valuable suggestions are offered to the hospital managers and further related studies. This study’s results further contribute to providing recommendations for the hospital management as well as the government concerning on factors affecting the healthcare workers’ job performance, especially at the age of a crisis such as the COVID-19 pandemic.